2022
DOI: 10.1186/s12986-022-00656-6
|View full text |Cite
|
Sign up to set email alerts
|

Is the urinary iodine/creatinine ratio applicable to assess short term individual iodine status in Chinese adults? Comparison of iodine estimates from 24-h urine and timed-spot urine samples in different periods of the day

Abstract: Background Urinary iodine concentration (UIC) is routinely used to evaluate the population iodine status while the uniform method for the individual level assessment is uncertain. Objectives To explore the 24-h urinary iodine excretion (UIE) in five different periods of the day and the corresponding prediction equations respect by the use of creatinine-corrected UIC. Methods We collected 24-h, spot and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…At the population level, iodine status is typically evaluated by the MUIC from spot urine samples [15] . However, at an individual level, spot urine iodine levels may not accurately re ect iodine status due to signi cant day-to-day and within-day variations in urine iodine concentrations [17][18] . Currently, 24-hour UIE is considered a quasi-reference standard for assessing individual-level iodine status because it reduces hydration-dependent variations in iodine excretion [16] .…”
Section: Discussionmentioning
confidence: 99%
“…At the population level, iodine status is typically evaluated by the MUIC from spot urine samples [15] . However, at an individual level, spot urine iodine levels may not accurately re ect iodine status due to signi cant day-to-day and within-day variations in urine iodine concentrations [17][18] . Currently, 24-hour UIE is considered a quasi-reference standard for assessing individual-level iodine status because it reduces hydration-dependent variations in iodine excretion [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on healthy Swiss volunteers aged 4-60 years found that the UIC circadian rhythm of random urine samples increases from noon to midnight; therefore, collecting urine samples between 8:00 a.m. and 11:00 a.m. seems reasonable [28]. Some studies have pointed out that collecting the frst void is not recommended due to the difculty in collection [29]. Instead, fasting urine collection may impact the accuracy of the assessment of iodine nutritional status in morning urine samples [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The Knudsen equation was used to estimate 24-h urinary iodine excretion (UIE) among Chinese adults, which was the same as in Andersson ’s study in Switzerland 25 . Furthermore, our previous study showed that the Knudsen equation was the best to estimate the 24-h UIE among Chinese adults except in the morning 26 . The 24-h sodium excretion was calculated like iodine 25 , 27 .…”
Section: Methodsmentioning
confidence: 99%